Design, Synthesis, and Antitumor Activity Study of All-Hydrocarbon-Stapled B1-Leu Peptides - Su, Zhen; Liu, Chao; Cong, Wei; He, Shipeng; Su, Li; Hu, Honggang (Frontiers in Chemistry, 2022)
B1-Leu peptide is a structural optimization compound derived from lysine-rich and phenylalanine-rich antimicrobial peptide (AMP) Cathelicidin-BF. It has shown promising anti-bacterial and anti-tumor biological activity. However, linear peptides are not the best choice for novel drug development due to their poor medicinal properties. In this study, various all-hydrocarbon stapled B1-Leu derivatives were designed and synthesized. Their secondary structure, protease stability, anti-tumor and hemolytic activity were also investigated to evaluate their clinical value for cancer therapy. Among them, B1-L-3 and B1-L-6 showed both superior stability and anti-tumor activity, showing that they are promising lead compounds for the development of novel cancer therapeutics.